2001
DOI: 10.1152/ajpendo.2001.280.5.e788
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of β-cell mass to substrate oversupply: enhanced function with normal gene expression

Abstract: Although type 2 diabetes mellitus is associated with insulin resistance, many individuals compensate by increasing insulin secretion. Putative mechanisms underlying this compensation were assessed in the present study by use of 4-day glucose (GLC; 35% Glc, 2 ml/h) and lipid (LIH; 10% Intralipid + 20 U/ml heparin; 2 ml/h) infusions to rats. Within 2 days of beginning the infusion of either lipid or glucose, plasma glucose profiles were normalized (relative to saline-infused control rats; SAL; 0.45% 2 ml/h). Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
120
4
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 46 publications
11
120
4
3
Order By: Relevance
“…No differences in the expression of islet-specific genes such as insulin, glucokinase, and Pdx-1 were observed in rats infused with glucose or Intralipid versus controls (27) or in cyclin genes involved in ␤-cell proliferation in glucose-infused mice (31). We observed an increase in insulin mRNA expression in glucose-infused rats, which was not observed in animals also receiving Intralipid.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…No differences in the expression of islet-specific genes such as insulin, glucokinase, and Pdx-1 were observed in rats infused with glucose or Intralipid versus controls (27) or in cyclin genes involved in ␤-cell proliferation in glucose-infused mice (31). We observed an increase in insulin mRNA expression in glucose-infused rats, which was not observed in animals also receiving Intralipid.…”
Section: Discussioncontrasting
confidence: 59%
“…The lack of effects of glucose and Intralipid on insulin secretion is in marked contrast with the results of previous studies using continuous infusion protocols (15,21-29). While Sako and Grill (22) glucose infusion reduced GSIS, in other studies a marked enhancement was observed (27)(28)(29). Thibault et al (23) observed that sustained hyperglycemia enhances insulin secretion in both normal and hyperglycemic rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When b-cell compensation can adequately meet the insulin demands of the body, normoglycemia is maintained. [5][6][7] However, in susceptible individuals perhaps with genetic defects and/or environmental insults, the b-cells cannot meet the metabolic demands, ultimately resulting in type 2 diabetes. [8][9][10][11] A previous study by Gunton et al 12 reported results of gene expression profiling analyses on islets of humans with type 2 diabetes, and found a significant decrease in aryl-hydrocarbon-receptor nuclear translocator (ARNT)/hypoxiainducible factor-1b (HIF-1b) expression in these islets.…”
mentioning
confidence: 99%
“…Cross-sectional [34] and longitudinal studies in humans [35] and in experimental studies in animals [36,37] have shown that a reduction in insulin sensitivity is usually associated with a compensatory increase in insulin secretion to maintain glucose homeostasis. This observation has led to the concept of ªdisposition indexº of insulin (DI), which implies that the product of insulin secretion and insulin sensitivity should remain constant for a given population (or individual) if glucose homeostasis is to remain unaltered [38,39].…”
Section: Discussionmentioning
confidence: 99%